DIGNIFIED JUSTICE PRESPECTIVE ON THE DEVELOPMENT OF MILITARY LAW IN INDONESIA: WHAT AND HOW? - Kriswanto, Kriswanto (Faculty of Law, Universitas Pekalongan, 2024)
Military law in Indonesia plays a crucial role in maintaining the country's order and security, with the perspective of dignified justice being highly relevant to ensure the protection of human rights for soldiers and justice in military legal processes. This research aims to analyze the development of military law in Indonesia from the perspective of dignified justice, as well as to identify challenges and opportunities in integrating the principles of dignified justice into the Indonesian military legal system. This study employs normative legal research methods with a conceptual and legislative approach. Data sources include primary, secondary, and tertiary legal materials collected through literature studies, then qualitatively analyzed using deductive-inductive reasoning to understand the concept of dignified justice and its application in Indonesian military law. The research findings indicate that the development of military law in Indonesia, viewed from the perspective of dignified justice, shows a complex and dynamic evolution since the era of independence. Continuous efforts are being made to build a military legal system that aligns with the principles of democracy, human rights, and the rule of law, as reflected in regulatory changes such as Law No. 34/2004 and Law No. 25/2014. Although there are still challenges in implementation, particularly related to military court jurisdiction, gender equality, and balancing national defense interests with individual rights protection, these developments reflect the efforts to realize dignified justice in the military context. This process also opens significant opportunities, including comprehensive military law reform, strengthening military professionalism, and developing a more humanistic military doctrine, although it still requires continuous evaluation and refinement to achieve a balance between national security and respect for human dignity.